Urgensi Penguasaan Bahasa Inggris dalam Perekrutan Calon Pelaut di PT. Equinox Bahari Utama - Nabila Aurel Salsabila; Elly Kusumawati; Edi Kurniawan; Indah Ayu Johanda Putri (Pusat Riset dan Inovasi Nasional, 2025)
This research discusses the urgency of mastering English in the recruitment process of prospective sailors at PT. Equinox Bahari Utama. In the era of globalization and the international maritime industry, proficiency in English has become an absolute requirement for sailors to meet communication standards on board. The objectives of this research are: (1) to determine the recruitment criteria standards for prospective sailors at PT. Equinox Bahari Utama, and (2) to understand the strategies of prospective sailors in mastering English for successful recruitment at PT. Equinox Bahari Utama. This research uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation during field practice in the Recruitment Division of PT. Equinox Bahari Utama. The research results show that English is a determining factor in all stages of the selection process, from interviews to online tests (Marlins and CES). The SWOT analysis reveals that the company's main strength is the implementation of high standards for English proficiency, but challenges remain in the form of a lack of training. The strategies used by prospective sailors to improve their English proficiency include courses, reading ship safety manuals, speaking practice, and interview simulations.